Pengaruh Pengetahuan Keuangan dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Keluarga : Studi Kasus Pada Warga Kelurahan Kaligangsa Kulon, Kecamatan Brebes, Kabupaten Brebes - Dewi Sri Wahyuningsih; Ninik Dwi Atmini; Heru Yulianto; Hesti Ristanto (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The purpose of this study: 1). To determine and explain the influence of financial knowledge on family financial management behavior, 2). To determine and explain the influence of financial attitudes on family financial management behavior, 3). To determine and explain the influence of financial knowledge and financial attitudes on family financial management behavior. The population in this study were residents of Kaligangsa Kulon Village, Brebes District, Brebes Regency who were 17 years old and over and totaled 5879 people. The study was conducted based on probability sampling techniques, simple random sampling. The results of the study can be concluded that: 1). Financial knowledge does not affect family financial management behavior, 2). Financial attitudes have a positive and significant effect on family financial management behavior, 3). Financial knowledge and financial attitudes have a positive and significant effect on family financial management behavior.